Re-evaluating the collaborative process between Luciano Berio and Cathy Berberian for Sequenza III (1965-66) and its critical reception in North America, the United Kingdom and Australia - Beretin, Nena (Analitica. Rivista online di studi musicali, 2023)
This paper discusses the importance of collaborative projects and the extent of the symbiotic relationship between Luciano Berio and Cathy Berberian for the compositional process and the performance realisation of Sequenza III (for voice, 1965). The twentieth-century scholarly and critical attention of the Berio/Berberian team, however, appears to focus primarily on Berio as ‘the composer’ rather than on the important multidimensional input of Berberian. Drawing on published interviews with Berio and Berberian, this paper analyses the compositional process of Sequenza III to show that the symbiotic relationship depends on Berio’s vocal ideas and, equally, Berberian’s illustration of new vocal techniques. I argue that Berberian was integral in the compositional processes and hence, an equal contributor to the success of this work. Another area of discussion in this paper concerns Berberian’s performance of Sequenza III. It is widely acknowledged that the success of a composer’s work is dependent to a large extent on the talent and the virtuosic attributes of the musician/vocalist in the performance realisation. The teaming of a high-profile composer with a renowned performer ensures optimum press coverage. By the 1960s, Berberian had a reputation (with the press) as a virtuoso of traditional classical vocal repertoire and as a major new music exponent. In realising the ‘cult’ status of Berberian, this paper assesses the critical reception in North America, the United Kingdom, and Australia of her performances to later vocalists including Luisa Castellani. This study shows that in tailoring Sequenza III exclusively to Berberian’s personality, wit, and vocal capabilities present multi-level challenges to subsequent singers.